Investigating the Role of CG8093 in Drosophila Female Germline Stem Cells - Cavallero, Michael Louis (East Carolina University, 2023)
Cell division and differentiation are imperative for the maintenance of living organisms. Germ cells, which serve as the progenitor cells necessary to create oocytes and sperm, are maintained in many organisms by the activity of a tissue-resident stem cell population called germline stem cells (GSC). To understand how germ cells are maintained, we used the well-characterized model reproductive tissue, the Drosophila ovary, which contains approximately 45 GSCs in young flies. Advances in whole genome sequencing have recently made possible the identification of the GSC transcriptome. In this data set, we identified an uncharacterized coding gene (CG8093) that is enriched specifically in GSCs during oogenesis. CG8093 is a predicted acid lipase that is regulated by diet. When cells experience an abundance of dietary sugars, the downregulation of CG8093 is observed, suggesting that CG8093 serves as a cellular sensor of nutrient availability. However, the role of CG8093 specifically in the GSCs for the division and differentiation of germ cells is not known. Here, I show that depletion of CG8093 in germ cells results in a complete block to GSC establishment, manifesting as agametic ovaries. In contrast, depletion in differentiated germ cells does not alter oocyte differentiation. This data suggests that CG8093 is a key player in the division and differentiation of GSCs in Drosophila melanogaster. Understanding the complexity of proteins needed for successful division and differentiation of germ cells is necessary for understanding how these cells are maintained to support organismal fertility.
Keywords: Differentiation, Metabolism